Local nearrings with multiplicative Shmidt group - Raievska, I. Yu.; Raievska, M. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.6 We propose a classification of finite local nearrings with multiplicative Shmidt group.Moreover, it is shown that there are no nearrings with identity on the Shmidt groups.